Editorial: Novel Perspectives on Status in Global Politics - Ali Bilgic; Miriam Prys‐Hansen; Clemens Hoffmann (Politics and Governance, 2025)
This thematic issue advances debates on status in international relations (IR) by integrating novel empirical research with innovative theoretical perspectives. It moves beyond traditional power-centric views, highlighting the social and relational dimensions of status-seeking as a diplomatic and foreign policy practice. The contributions explore, for instance, how states pursue status through cooperation, adherence to international norms, and strategic identity management. By examining diverse cases, including non-traditional status-seekers, this collection of contributions underscores the multifaceted nature of status-seeking, involving both material and ideational factors, and enriches the literature on status in IR, offering new insights into the complex dynamics of international hierarchy and state behaviour. In this editorial, we highlight the main findings and give an outlook on the overarching contribution to IR research.